2016
DOI: 10.2989/rhm.2016.6.1.4.1292
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable restaurants: A research agenda

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles Research in Hospitality Management is co-published by NISC (Pty) Ltd and Routledge, Taylor & Francis Group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 15 publications
(20 reference statements)
0
20
0
2
Order By: Relevance
“…This article tries to fill the gap already identified in the literature (Jacobs & Klosse, 2016) by presenting and discussing evidence from two empirical cases where this link between macro-and micro-levels of food sustainability were explored. The first case takes place in a major global cosmopolitan city -Berlin, Germany -where a new restaurant experimented with an internal exercise of adopting ten self-constructed sustainable food principles.…”
Section: Introductionmentioning
confidence: 99%
“…This article tries to fill the gap already identified in the literature (Jacobs & Klosse, 2016) by presenting and discussing evidence from two empirical cases where this link between macro-and micro-levels of food sustainability were explored. The first case takes place in a major global cosmopolitan city -Berlin, Germany -where a new restaurant experimented with an internal exercise of adopting ten self-constructed sustainable food principles.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, previous studies have focused on specific aspects of sustainable restaurants such as exploring customers perception and intentions toward sustainable food/restaurants (Kim et al, 2015;So-young Kim et al, 2016;Shin et al, 2018;Barone et al, 2019;Kim & Hall, 2020), management and stakeholder perception (Jang et al, 2017), and green supply management (Wang et al, 2013). Although some studies attempted to investigated sustainable restaurant operations (such as Jacobs & Klosse, 2016;Cantele & Cassia, 2020), these studies have not adopted a holistic approach that addresses various business aspects. In a similar vein, Jacobs and Klosse (2016) reported that despite a large number of studies on tourism and hospitality sustainability, there is a paucity of research on sustainable food services.…”
mentioning
confidence: 99%
“…Although some studies attempted to investigated sustainable restaurant operations (such as Jacobs & Klosse, 2016;Cantele & Cassia, 2020), these studies have not adopted a holistic approach that addresses various business aspects. In a similar vein, Jacobs and Klosse (2016) reported that despite a large number of studies on tourism and hospitality sustainability, there is a paucity of research on sustainable food services. Likewise, Jang et al (2017) disputed that most studies on sustainable restaurants lacked proper theoretical grounding and failed to provide adequate frameworks that support foodservice sustainability.…”
mentioning
confidence: 99%
“…В процесі приготування кулінарної продукції необхідно суворо дотримуватися правил санітарного режиму на виробництві, вести суворий контроль за якістю страв. З метою підвищення рівня якості та культури обслуговування, а також конкурентоздатності на світовому ринку, підприємства готельно-ресторанного бізнесу повинні пропонувати не лише високий рівень комфорту, але й широкий спектр додаткових послуг, які, зазвичай, потребують збільшення витрат енергетичних ресурсів [2,3].…”
unclassified
“…Проведено ряд досліджень [2,3,4,6], задля вирішення проблеми енергоефективності закладів готельноресторанного бізнесу. Серед запропонованих рішень -перехід до будівництва екоготелів, які енергетично є незалежними від держави та забезпечують себе альтернативними енергоресурсами (енергія сонця, вітру).…”
unclassified